2014
DOI: 10.3762/bjoc.10.9
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of (+)-grandiamide D, dasyclamide and gigantamide A from a Baylis–Hillman adduct: A unified biomimetic approach

Abstract: SummaryA unified strategy was followed for the synthesis of three putrescine bisamides, (+)-grandiamide D, dasyclamide and gigantamide A, isolated from leaves of Aglaia gigantea, by making use of a common synthetic intermediate prepared by the Baylis–Hillman reaction. Asymmetric synthesis of the natural (+)-grandiamide D was accomplished from camphor sultam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Finally, acid-catalyzed deprotection of a ketal moiety in (+)-diamide 8 furnished the desired natural product (+)-grandiamide D (9) in 77% yield (98% ee by HPLC). The analytical and spectral data obtained for synthetic product was in complete agreement with the reported data for natural product 3,5 and the chemoenzymatic synthesis of (+)-grandiamide D (9) was accomplished in nine steps in 12% overall yield. The natural products (-)-tulipalin B (10) and (+)-spirathundiol (11) have been isolated from Tulipa gesneriana and Spiraea thunbergii Sieb.…”
Section: Syn Thesissupporting
confidence: 83%
See 2 more Smart Citations
“…Finally, acid-catalyzed deprotection of a ketal moiety in (+)-diamide 8 furnished the desired natural product (+)-grandiamide D (9) in 77% yield (98% ee by HPLC). The analytical and spectral data obtained for synthetic product was in complete agreement with the reported data for natural product 3,5 and the chemoenzymatic synthesis of (+)-grandiamide D (9) was accomplished in nine steps in 12% overall yield. The natural products (-)-tulipalin B (10) and (+)-spirathundiol (11) have been isolated from Tulipa gesneriana and Spiraea thunbergii Sieb.…”
Section: Syn Thesissupporting
confidence: 83%
“…8a Acid-catalyzed hydrolysis of (+)-acetate 2 to the corresponding (+)-alcohol 1 followed by TBDMS-protection provided (-)-silyl ether 3 in 85% yield over two steps. The DIBAL reduction of (-)-diester 3 to the corresponding (+)diol 4 followed by TBAF induced desilylation supplied the desired enantiomerically pure (+)-artabotriol (5) in 67% yield over two steps. The analytical and spectral data obtained for synthetic (+)-artabotriol (5) was in complete agreement with the reported data for natural product (-)artabotriol (5) 2 and the chemoenzymatic first synthesis of (+)-artabotriol (5) was accomplished in five steps in 31% overall yield.…”
Section: Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…Grandiamide D (324), gigantamide A (328) and dasyclamide (327) were isolated by Duong et al from the leaves of Aglaia gigantean [90]. Very recently Ilangovan and Saravanakumar reported the synthesis of these natural products by using MBH adduct 320 as the common intermediate [91]. They showed that the MBH reaction of ethyl acrylate with aldehyde 318 afforded the racemic adduct 320 which was then converted to the intermediate 323 and dasyclamide 327 via EDCI coupling reaction.…”
Section: Grandiamidementioning
confidence: 99%